Solid state - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2024)
By simple observation of matter, it could be seen that everything enters into solid state on freezing. This information could be used to make strong masses that could be used to build homes and offices.The reason for this paper is to put forward an observation by me. This observation is that everything enters into solid state on freezing.  An example of it is water [1].